Digital addiction and anti-mattering: the serial mediation role of state hope and flourishing - Zeynep Demirtaş; Selim Uylas; Serhat Arslan; Fatih Yılmaz; Celalettin Çelebi; Nihan Arslan; Sümeyra Dilek Uylas (Institute of Advanced Engineering and Science, 2026)
This study examines the serial mediating roles of state hope and flourishing in the relationship between digital addiction (DA) and anti-mattering (AntiM). Using a cross-sectional correlational design, data were collected from 461 university students in Turkey. Participants completed the digital addiction scale (DAS), anti-mattering scale (AntiMs), flourishing scale (FS), and state hope scale (SHS). The hypothesized model was tested using partial least squares structural equation modeling (PLS-SEM). Measurement and structural models were evaluated in terms of reliability, validity, path coefficients, and predictive relevance. Bootstrapping procedures were applied to test the significance of direct and indirect effects. The findings indicate that state hope and flourishing significantly mediate the relationship between DA and AntiM. Specifically, higher levels of DA are associated with lower state hope and reduced well-being, which in turn increase feelings of AntiM. These results reveal important psychological mechanisms underlying the negative effects of DA and highlight the protective role of positive psychological resources. The study offers valuable implications for future research and intervention programs aimed at reducing DA and promoting well-being.